Cerebrospinal Fluid Studies in Kenyan Children with Severe Falciparum Malaria. - Mturi, N; Keir, G; Maclennan, C; Ross, A; Willis, A; Elford, B; Berkley, J; Newton, C (2008)
The pathogenesis of the neurological complications of Plasmodium falciparum malaria is unclear. We measured proteins and amino acids in paired plasma and cerebrospinal fluid (CSF) samples in children with severe falciparum malaria, to assess the integrity of the blood brain barrier (BBB), and look for evidence of intrathecal synthesis of immunoglobulins, excitotoxins and brain damage. METHODS: Proteins of different molecular sizes and immunoglobulins were measured in paired CSF and plasma samples in children with falciparum malaria and either impaired consciousness, prostrate, or seizures. RESULTS: The ratio of CSF to plasma albumin (Q(alb)) exceeded the reference values in 42 (51%) children. The CSF concentrations of the excitotoxic amino acid aspartate and many non-polar amino acids, except alanine, were above the reference value, despite normal plasma concentrations. IgM concentrations were elevated in 21 (46%) and the IgM index was raised in 22 (52%). Identical IgG oligoclonal bands were found in 9 (35%), but only one patient had an increase in the CSF IgG without a concomitant increase in plasma indicating intrathecal synthesis of IgG. CONCLUSIONS: This study indicates that the BBB is mildly impaired in some children with severe falciparum malaria, and this impairment is not confined to cerebral malaria, but also occurs in children with prostrate malaria and to a lesser extent the children with malaria and seizures. There is evidence of intrathecal synthesis of immunoglobulins in children with malaria, but this requires further investigation. This finding, together with raised level of excitotoxic amino acid aspartate could contribute to the pathogenesis of neurological complications in malaria.